Optimization of friction welding of tube-to-tube plate using an external tool by Taguchi method and genetic algorithm - Senthil Kumaran, S.; Muthukumaran, S.; Vinodh, S. (International journal of advanced manufacturing technology, 2011)
Numerous advancements have been occurring in the field of materials processing. Friction welding is an important solid-state joining technique. In this research project, friction welding of tube-to-tube plate using an external tool (FWTPET) has been performed, and the process parameters have been prioritized using Taguchi’s L 27 orthogonal array. Genetic algorithm (GA) is used to optimize the welding process parameters. The practical significance of applying GA to FWTPET process has been validated by means of computing the deviation between predicted and experimentally obtained welding process parameters.